Technical Note: A novel dosimeter improves total skin electron therapy surface dosimetry workflow. Issue 6 (19th April 2020) - Tendler, Irwin I.; Bruza, Petr; Jermyn, Michael; Soter, Jennifer; Sharp, Gregory; Williams, Benjamin; Jarvis, Lesley A.; Pogue, Brian; Gladstone, David J.
Abstract: Purpose: The novel scintillator‐based system described in this study is capable of accurately and remotely measuring surface dose during Total Skin Electron Therapy (TSET); this dosimeter does not require post‐exposure processing or annealing and has been shown to be re‐usable, resistant to radiation damage, have minimal impact on surface dose, and reduce chances of operator error compared to existing technologies e.g. optically stimulated luminescence detector (OSLD). The purpose of this study was to quantitatively analyze the workflow required to measure surface dose using this new scintillator dosimeter and compare it to that of standard OSLDs. Methods: Disc‐shaped scintillators were attached to a flat‐faced phantom and a patient undergoing TSET. Light emission from these plastic discs was captured using a time‐gated, intensified, camera during irradiation and converted to dose using an external calibration factor. Time required to complete each step (daily QA, dosimeter preparation, attachment, removal, registration, and readout) of the scintillator and OSLD surface dosimetry workflows was tracked. Results: In phantoms, scintillators and OSLDs surface doses agreed within 3% for all data points. During patient imaging it was found that surface dose measured by OSLD and scintillator agreed within 5% and 3% for 35/35 and 32/35 dosimetry sites, respectively. The end‐to‐end time required to measure surface dose during phantom experiments for a single dosimeter was 78 and 202 sec for scintillator and OSL dosimeters, respectively. During patient treatment, surface dose was assessed at 7 different body locations by scintillator and OSL dosimeters in 386 and 754 sec, respectively. Conclusion: Scintillators have been shown to report dose nearly twice as fast as OSLDs with substantially less manual work and reduced chances of human error. Scintillator dose measurements are automatically saved to an electronic patient file and images contain a permanent record of the dose delivered during treatment.